617. Physician Perspective: Utilization of Advanced Practice Providers (APPs) in the ID Workforce. (31st December 2020) - Beieler, Alison M; Beieler, Alison M; Yoke, Leah H; Yoke, Leah H; Liu, Catherine; Pergam, Steven A; Wald, Anna; Wald, Anna; Dhanireddy, Shireesha; Dhanireddy, Shireesha
Abstract: Background: Applicants entering Infectious Disease (ID) fellowships are declining and shortages of ID physicians is a challenge recognized by the clinical workforce and Infectious Diseases Society of America (IDSA). There is increased awareness of more Advanced Practice Providers (APPs) being used within ID to expand and extend existing practices. However, little is known about APP utilization, APP clinical scope of practice, specific roles, and opportunities for education. Methods: To evaluate physician perspectives on APP utilization in ID, we created an anonymous and voluntary survey using the REDCap data tool that was distributed by social media, key stakeholder emails, and IDSA online community forum between 12/1/2019-1/31/2020. In addition to collecting geographic information and the type of ID practice, participants were also surveyed about the use of APPs and any perceived barriers that may limit their use. Results: 218 practicing ID physicians responded to the survey (Figure 1). 155 (71%) physicians work with APPs in their current practice (Figure 2); specifically, 56 (27%) with 1 APP, 62 (30%) with 2-4 APPs, 28 (13%) with 5-9 APPs, and 11 (5%) with > 10 APPs. Of respondents, 104 (48%) practiced at University/Medical schools, 80 (37%) in hospitals/clinics, and 28 (13%) in private practice (Table 1); most work in adult inpatient/outpatient ID. The main reasons selected by respondents for not using APPs in their practice included concerns around a lack of formal ID training 22 (15%), lack of time/lack of ability to assist with APP training 29 (20%), practice is already sufficiently staffed 19 (13%), and concern for physician revenue loss 16 (11%) (Table 1). Figure 1. Physician Responses by Region, n = 218 Figure 2. Physicians Utilizing APPs in Practice, n = 210 (*no response, 8) Table 1. Physician ID Practice Type, Setting, and Concerns Conclusion: Results suggest that while collaboration between ID physicians and APPs exists to meet current needs, a lack of ID training is a limiting factor. Our findings demonstrate there is an opportunity for formal ID education and resource development both to enhance APPs clinical skills and address perceived knowledge gaps. Inclusion of APPs in the ID workforce may allow physicians to expand ID care into more resource limited areas to continue to provide high quality patient care. Disclosures: Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis)